PELAKSANAAN SISTEM OUTSOURCING TENAGA KERJA CV. BUMI NUSANTARA DI PT. ITCI HUTANI MANUNGGAL - Solikin, Solikin (The Juris, 2017)
Workers recruited by employers 'service providers also obtain the same rights as contracts with respect to wage and welfare protection, terms of employment, and disputes arising with other workers in workers' service companies as required by Law No. 13 of 2003 on Manpower). Employers providing employment services, from employers, both parties shall enter into written agreements.